Group Work That Examines Systems of Power With Young People: Youth Participatory Action Research. Issue 2 (3rd April 2017) - Cook, Amy L.; Krueger-Henney, Patricia
Abstract : Youth-led group work shifts power dynamics and repositions youth as leaders in driving the learning they envision for themselves. This shift calls into question how group facilitators measure outcomes of youth empowerment groups. Youth participatory action research (YPAR) has expanded the field of knowledge production by creating shared spaces where youth participants co-create research agendas and processes that are guided by their lived experiences and expertise, and generate data-driven action to address social problems. We propose applications of YPAR as both an emancipatory epistemology and methodology to inform group work research.